Investigation of the impact of PM2.5 on the ciliary motion of human nasal epithelial cells. (October 2019) - Jia, Jiaxin; Xia, Jiao; Zhang, Ruxiang; Bai, Yi; Liu, Shen; Dan, Mo; Li, Ting; Yan, Tenglong; Chen, Li; Gong, Shusheng; Niu, Piye; Chen, Tian
Abstract: Nasal epithelium provides a physical barrier to potentially harmful stimuli. Cilia, which is on the apical side of the human nasal epithelial cells (HNEpCs), plays a critical role in removing inhaled harmful matter. Ciliary beat frequency (CBF) and ciliary beat pattern (CBP) are the two important indicators for ciliary beat function. However, impacts of the fine particulate matter (PM2.5 ) on CBF and CBP are still unknown. We aimed to evaluate the impact of PM2.5 on the ciliary beat function of the HNEpCs and its potential mechanisms. After exposed to PM2.5 for 12 h, cilia of HNEpCs were in disordered arrangement. The ciliary coverage rate was decreased after PM2.5 exposure of a series of concentration, while the proportion of basal cells was continuously increased and could be observed on the apical side of the HNEpCs which is hardly be observed without PM2.5 exposure. PM2.5 increased the CBF after 12 h exposure, while 24 h exposure increased the CBF at the relative lower dosage groups and then made a decrease at relative higher dosage groups. CBF were classified into two different types, which had different changes following PM2.5 exposure. CBP showed significant changes characterized as the increased dyskinesia index. Total levels of cellular ATP and the mitochondrial membrane potential were decreased following 12 h exposure of PM2.5, while no change was found in O2 consumption. In conclusion, PM2.5 impact the ciliary beat function of HNEpCs, and the mitochondrial dysfunction might play an important role in it. Highlights: PM2.5 decreased the cilia, destroyed the ciliary morphology and increased proportion of basal cells. PM2.5 changed the ciliary beat frequency (CBF) and there was a difference between 12 h and 24 h exposure. PM2.5 disrupted the ciliary beat pattern (CBP), which proceeded that of CBF. PM2.5 led mitochondrial dysfunction and morphological damage of HNEpCs.